N, N-dimethyl-triarylmethanolation as a versatile approach for multiresponsive emission/absorption opposite materials with capability as naked-eye alcohol and C–H acidity indicator. (April 2023) - Su, M.; Xiao, H.; Shi, Q.X.; Sheng, Y.J.; Li, D.L.; Wan, W.M.
Abstract: Emission (A)/absorption (B) opposite material (A∪B = Ω and A∩B = Ø) represents a novel material with potential applications as stimuli-responsive material, attributed to its dual responsive properties on both emission and absorption. Here, we demonstrate a N, N -dimethyl-triarylmethanolation strategy as a versatile approach for the molecular design of emission/absorption opposite materials with intriguing aggregation-induced emission, amorphization-induced emission, multiresponsive behaviors. Investigations on the structure–property relationship reveal that N, N -dimethyl-triarylmethanol moiety is essential to respond to stimuli including strong acid (HCl), weak acid (silica gel), water, alcohol, and C–H (acetylacetone (AcAc) and dimethyl malonate (DMM)). Attributed to the hydrogen bonding effect between N, N -dimethyl-triarylmethanol moiety and very weakly acidic alcohols or C–H acids, it exhibits capability as active hydrogen (alcohol and C–H) acidity indicator. Further applications in the fields of encryption and carbonyl compounds detection are demonstrated as well. This work, therefore, demonstrates the proof of concept of a novel emission/absorption opposite material, which might cause inspiration in different research areas. Graphical abstract: Insert Table of Contents artwork here. Image 1 Highlights: A proof of concept of emission/absorption opposite materials is demonstrated. A N, N -dimethyl-triarylmethanolation strategy for molecular design. Intriguing aggregation-induced emission and amorphization-induced emission. Naked-eye alcohol and C–H acidity indicator. Multiresponsive behaviors enable information encryption.